Prescott's Microbiology - Willey, Joanne M; Sherwood, Linda M Woolverton Christopher J; Woolverton, Christopher J (New York : McGraw-Hill, 2011)
The Eighth Edition continues to present material in short chapters organized thematically into nine separate sections. Shorter chapters are less daunting and more 'digestible' for most students. Furthermore, they offer the professor a greater degree of flexibility so that the order in which chapters are covered can be tailored to meet the needs of an individual class.
Includes Glossary G-1.; Credis C-1.; Index I-1.
Keywords: Applied microbiology; Microbial Metabolism; Microbial molecular biology; Botany